Analisis Perbankan Syariah di Bahrain : Sejarah, Regulasi, dan Kebijakan Anti Pencucian Uang (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the development of Islamic banking in Bahrain, with a focus on its history, regulatory framework, and Anti Money Laundering/Combating the Financing of Terrorism (AML/CFT) policies. Using a qualitative approach with descriptive analysis, the study examines various relevant literature sources, including books, academic journals, and official documents, to explore the evolution of the Islamic financial industry in Bahrain. The findings indicate that Bahrain has developed into one of the leading centers of Islamic finance in the Middle East since the establishment of its first Islamic bank in 1978. In 2007, Islamic banking assets in Bahrain reached US$20.1 billion, highlighting the country’s strategic role in the global Islamic finance sector. Bahrain provides a well-established regulatory framework through the Central Bank of Bahrain and the Bahrain Monetary Agency, with the implementation of standards set by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and the Financial Action Task Force (FATF) methodology to ensure Sharia compliance and the integrity of the financial system. The study also identifies ongoing challenges, including the need for improved inter-agency coordination and enhanced public literacy in Islamic finance to strengthen the sustainability of Bahrain’s Islamic financial industry.